A qualitative study on industry 4.0 competitiveness in Turkey using Porter diamond model - Gizem Erboz (Journal of Industrial Engineering and Management (JIEM), 2020)
Purpose: Industry 4.0 offers a new network approach by using advanced Information and Communication Technologies (ICT) and for manufacturing industries in particular. This paper analyzes the understandings of heavy manufacturing industry in Turkey about the concept of Industry 4.0 as well as its significance of in nation's competitiveness. The study applies in Porter's Diamond Model as a framework in order to provide a dynamic view of Industry 4.0 in nation's competitive advantage. Design/methodology/approach: The results of semi structured interviews are examined in the framework and common understandings are compared with existing literature. Findings: The analysis indicates that, the heavy manufacturing companies are aware of the topic of Industry 4.0 in general in terms of its definition, future aspects and possible benefits and challenges. It has been observed that factor conditions (labor and capital) are the most important aspects which affect development of Industry 4.0 competitiveness in Turkey. Although the country is still in initial stage on its competitive position; the effects of the government and some chances might increase its competitiveness in the future. Originality/value: Regarding different research on Industry 4.0, this paper gives an insight in development path of Industry 4.0 competitiveness especially for the developing countries. There is still lack of empirical research on nations' competitiveness on Industry 4.0; therefore, this paper deepens the concept for further research and action plans for the path of competitiveness.
Keywords: 650; Industry 4.0; technology; diamond model; competitiveness; manufacturing companies